Professional Skills and Soft Skills for LIS Professional in ICT Era - Machendranath, Dr.; Naik, Umesha; S., Devaraj; Kumari, Usha (Qualitative and Quantitative Methods in Libraries, 2019)
ICT tools empowered web-based library, which provides services to its user throughout computer networks. LIS Professional plays an important role in the field of Information Generation and dissemination to the end users based on information storage and retrieval process tools and techniques. In this paper the author explain the list of skill and its impact on LIS fields. This paper discusses the professional skills and soft skills required for the library professionals to provide effective services to the user’s community. Further it deliberates, the competencies required by the professionals such user’s needs assessment, application of new technology and development the non-print collection and also discusses the soft skills one should have to serve the users effectively such as communication skills, leadership skills, interpersonal skills, presentation skills etc.